Acetylacetone effectively controlled the secondary metabolites of Microcystis aeruginosa under simulated sunlight irradiation - Wang, Xiaomeng; Luo, Yixin; Zhang, Shujuan; Zhou, Lixiang (Journal of environmental sciences (China), 2024)
•Acetylacetone outperformed H2O2 in degrading algal metabolites under xenon irradiation.•Protein-like constituents were more susceptible to photodegradation by acetylacetone.•The biological toxicity of microcystin-LR was greatly reduced after photooxidation.•The photoactivity of acetylacetone was limited by alkaline pH, not by inorganic ions. Inactivation of cyanobacterial cells and simultaneous control of secondary metabolites is of significant necessity for the treatment of cyanobacteria-laden water. Acetylacetone (AcAc) has been reported a specific algicide to inactivate Microcystis aeruginosa (M. aeruginosa) and an effective light activator to degrade pollutants. This study systematically investigated the photodegradation ability of AcAc under xenon (Xe) irradiation on the secondary metabolites of M. aeruginosa, mainly algal organic matter (AOM), especially toxic microcystin-LR (MC-LR). Results showed that AcAc outperformed H2O2 in destructing the protein-like substances, humic acid-like matters, aromatic proteins and fulvic-like substances of AOM. For MC-LR (250 µg/L), 0.05 mmol/L AcAc attained the same degradation efficiency (87.0%) as 0.1 mmol/L H2O2. The degradation mechanism of Xe/AcAc might involve photo-induced energy/electron transfer and formation of carbon center radicals. Alkaline conditions (pH > 9.0) were detrimental to the photoactivity of AcAc, corresponding to the observed degradation rate constant (k1 value) of MC-LR drastically decreasing to 0.0013 min−1 as solution pH exceeded 9.0. The PO43− and HCO3− ions had obvious inhibition effects, whereas NO3− slightly improved k1 value from 0.0277 min−1 to 0.0321 min−1. The presence of AOM did not significantly inhibit MC-LR degradation in Xe/AcAc system. In addition, the biological toxicity of MC-LR was greatly reduced after photoreaction. These results demonstrated that AcAc was an alternative algicidal agent to effectively inactivate algal cells and simultaneously control the secondary metabolites after cell lysis. Nevertheless, the concentration and irradiation conditions should be further optimized in practical application. [Display omitted]